Cationic Dye Modified Sawdust as Electrode Modifier for Electrochemical Detection of Anions. Issue 2 (10th January 2019) - Ngana, Beaufils Ngatchou; Dedzo, Gustave Kenne; Nanseu‐Njiki, Charles Peguy; Ngameni, Emmanuel
Abstract: Because of its chemical properties, sawdust displays poor anionic exchange capacity. Here we demonstrate that sawdust modification with methylene blue (MB) dye represents an interesting and facile alternative to render this natural biomaterial capable to accumulate anionic species. MB adsorption onto sawdust was monitored by cyclic voltammetry and experimental parameters carefully optimized. Under the ideal experimental conditions (composition of accumulation and desorption solution, accumulation and desorption time and the nature of the electrolytic solution), the adsorbed MB showed poor mobility, which results in the absence of the characteristic electrochemical signal of MB. The ability of the material to accumulate anionic species was thus evaluated using Fe(CN)6 3− as a model anions. The slow Fe(CN)6 3−/4− system recorded onto the electrode modified by pristine sawdust (P/SFE) become fast and reversible after immobilization of MB onto P/SFE (MB/SFE). Electrochemical impedance spectroscopy confirms this result through the spectacular decrease of charge transfer resistance after MB adsorption (from 83 kΩ on P/SFE to 637 Ω on MB/SFE). MB/SFE was applied to the electroanalysis of nitrites and a sensitivity of 7.4 μA mM −1 was obtained. Although this sensitivity was less important compared to that obtained on glassy carbon electrode (9.4 μA mM −1 ), the dye modified electrode displays by far the best reproducibility even at higher nitrite concentration. Abstract :